How an international ambidexterity strategy can address the paradox perspective on corporate sustainability: Evidence from Chinese emerging market multinationals. (27th February 2020) - Ciasullo, Maria Vincenza; Montera, Raffaella; Cucari, Nicola; Polese, Francesco
Abstract: Corporate sustainability (CS) is receiving considerable attention from emerging market multinational enterprises (EMNEs), playing an important role in the globalized market. However, theoretical and empirical knowledge about how EMNEs address CS is still scant, and the relationship between internationalization and CS has not been widely explored. This study aims to fill this gap, evaluating the relationship between an international ambidexterity strategy and CS in EMNEs, which highlighted the paradox perspective. Then we develop three hypotheses in which we argue how the dynamic capabilities underpinning international ambidexterity could be considered a driver of CS in EMNEs. We test the developed hypotheses against data from 300 Chinese EMNEs obtained by a survey. Our results contribute to shape ambidextrous international strategies and to consider CS as a springboard for the strategic intent to systematically and recursively outperform global competition. Testing a measurement scale of international ambidexterity, we suggest structural ambidexterity as a strategic option of internationalization that allows the achievement of economic, social, and environmental sustainability objectives.